1981
DOI: 10.1084/jem.153.6.1426
|View full text |Cite
|
Sign up to set email alerts
|

Identification of leukemia-associated inhibitory activity as acidic isoferritins. A regulatory role for acidic isoferritins in the production of granulocytes and macrophages.

Abstract: Acidic isoferritins have been identified as leukemia-associated inhibitory activity (LIA), which suppresses colony and cluster formation of colony-forming unit-granulocyte macrophages from normal donors but not from patients with leukemia. LIA was detected in all ferritin preparations tested, including ferritin isolated from normal heart, spleen, liver, and placental tissues, and from the spleens of patients with chronic myelogenous leukemia and Hodgkin's disease. Purified preparations of LIA were composed alm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
55
2
1

Year Published

1982
1982
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(59 citation statements)
references
References 40 publications
1
55
2
1
Order By: Relevance
“…Of these inhibitors, TNF-a (33, 34) and H-ferritin (35) are reported to be released from LC, especially from AMLcells. However, the present data showed that the TNF-a levels in all the LC-CMstudied were minimal or below the detectable limit, agreeing with a report of Griffin and colleagues (36), but contrasting with other reports in which LCfrom the majority of AMLpatients were shown to release considerable amounts of TNF-a (33,34). Causes of such discrepancy are not clear, but may be due mainly to differences in the cell source and the method of preparation of LC-CM.…”
Section: Effect Of Viable Lc and Lc-cmon Km-101 Cellscontrasting
confidence: 57%
“…Of these inhibitors, TNF-a (33, 34) and H-ferritin (35) are reported to be released from LC, especially from AMLcells. However, the present data showed that the TNF-a levels in all the LC-CMstudied were minimal or below the detectable limit, agreeing with a report of Griffin and colleagues (36), but contrasting with other reports in which LCfrom the majority of AMLpatients were shown to release considerable amounts of TNF-a (33,34). Causes of such discrepancy are not clear, but may be due mainly to differences in the cell source and the method of preparation of LC-CM.…”
Section: Effect Of Viable Lc and Lc-cmon Km-101 Cellscontrasting
confidence: 57%
“…Sala et al (31) were unable to confirm the original results of Broxmeyer et al (29) and since 1992 there has been little work on this inhibitory activity of ferritin.…”
Section: Ferritin As a Regulator Of Erythropoiesiscontrasting
confidence: 38%
“…A role for ferritin in the regulation of haemopoiesis, apparently unrelated to iron storage, was proposed by Broxmeyer et al (29) who showed that the protein responsible for a 'leukaemia-associated inhibitory activity' (LIA) was an acidic isoferritin. This protein fraction, and an acidic isoferritin preparation from the spleen of a patient with chronic myeloid leukaemia, suppressed colony formation in vitro of CFU-GM, BFU-E and CFU-GEMM progenitor cells from the marrows of normal donors, but was ineffective in marrow or blood from patients with acute leukaemia, myelodysplasia and some other haematological disorders.…”
Section: Ferritin As a Regulator Of Erythropoiesismentioning
confidence: 99%
“…For example, the H/L ratio is about 2/3 in liver isoferritins and about 4/1 or 5/1 in heart isoferritins (4). The H/L subunit ratio characteristic of a particular tissue may be altered during normal cellular differentiation or in pathological conditions such as iron overload or neoplasia (7,15,34). The functional significance of such changes in H/L subunit ratio is only beginning to be understood.…”
mentioning
confidence: 99%
“…It is the H subunitrich isoferritins which show the heaviest iron loading in human liver (3), but iron challenge of human monocytes preferentially stimulates L subunit synthesis (14) just as was noted for the rat. In addition, it is a glycosylated serum isoferritin with a high H/L subunit ratio (acidic isoferritin) which has been found to be associated with an inhibitory activity on normal myelopoiesis (7,27).…”
mentioning
confidence: 99%